SISTEM INFORMASI PENJUALAN BARANG PADA SEMESTA ART GALLERY - Waluyo, Tri; Retnoningsih, Dwi; Anwariningsih, Sri Huning (Gaung Informatika, 2012)
Technology in the business world increasingly plays an important role. One of them is the application of a computerized of sales information system on the company for the work efficiency. This ways is more and more often used because it useful for storage of data and make the search for data or information easier, in order avoid the usual dereliction that usually find in the manual storage systems. Various problems that often arise as a result of manually managing on Semesta Art Galery are: (a) the stock of goods in warehouse is difficult to be controlled, (b) high risk loss data of purchase and sales transaction, and (c) recording system of non-cash sales / credit is not optimal. The objectivity of the research is to build sales information system on Semesta Art Galery in case for: 1) change the manual sales system into computerized systems. 2) Increasing sales by adding non-cash sales menu / credits on software that is built so hoped non-cash sales system can increase the number of costumers, and 3)helps the staff in processing of goods sale data, supplier data reports, reports sales, and bill of sales transaction. This system is build using the waterfall method (the life cycle of software) and uses the programming language Visual Basic 6.0, SQL Server 7. based on results of testing system using Mc Call method, show a total value of the quality is 75.4% with the conclusion that: 1) the sales information system is easy to learn and operate by the user, 2) can run on hardware and operating systems that exist in the Semesta Art Gallery, 3) has good level in efficiency, very effective to minimize the errors that occur, and is hoped can be used as a tool to optimize sales system in the Semesta Art Gallery.